The α2,3-sialyltransferase encoded by myxoma virus is a virulence factor that contributes to immunosuppression. - Bérengère Boutard; Sophie Vankerckhove; Nicolas Markine-Goriaynoff; Mickaël Sarlet; Daniel Desmecht; Grant McFadden; Alain Vanderplasschen; Laurent Gillet (PLoS ONE)
Myxoma virus (MYXV) induces a lethal disease called Myxomatosis in European rabbits. MYXV is one of the rare viruses that encodes an α2,3-sialyltransferase through its M138L gene. In this study, we showed that although the absence of the enzyme was not associated with any in vitro deficit, the M138L deficient strains are highly attenuated in vivo. Indeed, while all rabbits infected with the parental and the revertant strains died within 9 days post-infection from severe myxomatosis, all but one rabbit inoculated with the M138L deficient strains survived the infection. In primary lesions, this resistance to the infection was associated with an increased ability of innate immune cells, mostly neutrophils, to migrate to the site of virus replication at 4 days post-infection. This was followed by the development of a better specific immune response against MYXV. Indeed, at day 9 post-infection, we observed an important proliferation of lymphocytes and an intense congestion of blood vessels in lymph nodes after M138L knockouts infection. Accordingly, in these rabbits, we observed an intense mononuclear cell infiltration throughout the dermis in primary lesions and higher titers of neutralizing antibodies. Finally, this adaptive immune response provided protection to these surviving rabbits against a challenge with the MYXV WT strain. Altogether, these results show that expression of the M138L gene contributes directly or indirectly to immune evasion by MYXV. In the future, these results could help us to better understand the pathogenesis of myxomatosis but also the importance of glycans in regulation of immune responses.